BIM content development : standards, strategies, and best practices - Weygant, Robert S., 1973- (Wiley, 2011)
"From the cutting-edge of technology comes this book on Building Information Modeling (BIM), the newest technology in the AEC industry that allows the professional to create 3D models of a building that includes much more data than a traditional 2D CAD file. Developing BIM Content explains the type of information that can go into a BIM model from a vendor-neutral perspective and explores different methods for organizing content. For anyone interested in creating feature-rich BIM object and models that work on any platform, this is a must-have reference"--